2018
DOI: 10.1111/ijfs.13953
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different solvents on total phenolic and total anthocyanin contents of Clitoria ternatea L. petal and their anti‐cholesterol oxidation capabilities

Abstract: Summary Clitoria ternatea (CT) petals have a high content of polyphenolic compounds, including anthocyanins, which protect against lipid oxidation. This research evaluated total phenolic content, total anthocyanin content and antioxidant activity of CT extracts obtained using distilled water, methanol, and/or water‐methanol combination (1:1) solvents after 6, 12 and 24 h soaking times. The predominant bioactive compounds of CT petals were kaempferol 3‐neohesperidoside (462.63 mg per 100 g), caffeoylmalic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
(60 reference statements)
0
19
0
Order By: Relevance
“…Therefore, when anthocyanins from blue pea flowers are extracted for food application, the use of hazardous organic solvents should be avoided (Khoo et al, 2017;Chemat et al, 2019). Several studies have used hydro alcoholic extraction [i.e., 37% ethanol (Jaafar et al, 2020), 50% ethanol (Pham et al, 2019), 50% methanol (Shen et al, 2019)] to extract anthocyanins from blue pea flower. However, FDA (2018) has categorised methanol as a class 2 solvent having inherent toxicity and ethanol as a class 3 solvent that should be limited by good manufacturing practices (GMP) and other quality-based requirements.…”
Section: Extraction Of Blue Pea Flower Anthocyaninsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, when anthocyanins from blue pea flowers are extracted for food application, the use of hazardous organic solvents should be avoided (Khoo et al, 2017;Chemat et al, 2019). Several studies have used hydro alcoholic extraction [i.e., 37% ethanol (Jaafar et al, 2020), 50% ethanol (Pham et al, 2019), 50% methanol (Shen et al, 2019)] to extract anthocyanins from blue pea flower. However, FDA (2018) has categorised methanol as a class 2 solvent having inherent toxicity and ethanol as a class 3 solvent that should be limited by good manufacturing practices (GMP) and other quality-based requirements.…”
Section: Extraction Of Blue Pea Flower Anthocyaninsmentioning
confidence: 99%
“…Some studies use a soaking step before extracting anthocyanins. However, Shen et al (2019) showed that soaking is not necessary when extracting anthocyanins from blue pea flowers using water. Soaking significantly reduced the TAC of the blue pea flower anthocyanin extract from 58.2 to 39.9 µg cyanidin-3-glucoside/mL when the petals were soaked in water for 24 h but there was no significant difference in the TAC of the blue pea flower anthocyanin extract when soaking was carried out for 6 and 12 h. The reason for the reduction of TAC due to soaking could be attributed to the increase of hydrolysis of anthocyanins when more water molecules are available in the matrix (Matsufuji et al, 2007;Marpaung et al, 2017).…”
Section: Extraction Of Blue Pea Flower Anthocyaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a reflection of the simplicity of the methodology which does not accurately represent human biological fluids. In order to overcome this methodological limitation, emulsion models have been developed as it has been which suggested that measures of antioxidant capacity using existing methodologies are not always translatable into an emulsion model which suggest a more potent effect of polyphenols (Zhang et al ., ; Lopez Prado et al ., ). Such models may provide a more representation of how antioxidants may behave in a biological or even a food system.…”
Section: Emulsion Models Assessing Capacitymentioning
confidence: 97%
“…Such models may provide a more representation of how antioxidants may behave in a biological or even a food system. Although it is not a universal model, the emulsion models offer a way of assaying, albeit in vitro , how antioxidants may interact and protect lipids including cholesterol and triglycerides, which are known factors within both human pathogenesis and food spoilage (Lopez Prado et al ., ).…”
Section: Emulsion Models Assessing Capacitymentioning
confidence: 97%